Risk correlation analysis of serum adiponectin (APN), D-dimer (DD) and the neutrophil‒lymphocyte ratio (NLR) with the prognosis of diabetic foot ulcer infection: Serum APN, D-D and NLR in prognosis of diabetic foot ulcer infection - Guo, Guodong; Zhang, Xiaohui; Fang, Peng; Li, Kangkanng; Wang, Chaoyang; Liu, Gang; Ma, Huijuan (Journal of Medical Biochemistry, 2025)
Objective: Investigating the connections between diabetic foot ulcer infection patients’ prognosis and disease severity, we measured serum adiponectin (APN), D-dimer (D-D), and the neutrophil-to-lymphocyte ratio (NLR). Methods: A total of 292 patients with diabetic foot ulcer infection admitted to our hospital from February 2024 to February 2025 were selected and divided into mild (n=95), moderate (n=139) and severe (n=58) patients according to the severity of the disease. The levels of serum APN, D-D and the NLR in patients with different severity levels were compared. To analyze serum APN, D-D and the NLR, patients were followed up for one year, and the prognoses of the patients were statistically analyzed. Results: Comparisons of the serum APN, D-D and NLR levels among patients with different severity, and the serum APN levels in moderate conditions were lower than those in patients with mild conditions (P<0.05). The serum APN of severe patients was 5.35±0.98, and that of moderate patients was 7.64±1.25, which was lower than that of mild patients (9.19±1.73; P<0.05), and the serum APN level of severe patients was lower than that of moderate patients (P<0.05). Comparisons of the serum D-D and NLR levels revealed that the serum D-D and NLR in severe patients were 3.49±0.72 and 2.86±0.58, respectively, and those in moderate patients were 3.02±0.63 and 2.24±0.46, respectively, both of which were greater than those in mild patients, which were 2.43±0.51 and 1.71±0.33 (P<0.05). The levels of serum D-D and the NLR were greater in severe patients than in moderate patients (P<0.05). According to Spearman correlation analysis, the severity of the disease in diabetic foot ulcer infection patients was positively connected with the serum D-D level and NLR (r=0.387, P<0.001; r=0.461, P<0.001) and negatively connected with the serum APN level (r=-0.414, P<0.001). ROC analysis revealed that the optimal cutoff values of the serum APN, D-D and NLR for predicting poor prognosis in patients were 5.73 mg/L, 3.06 mg/L and 2.12, respectively; the sensitivities were 78.57%, 82.14% and 85.71%, respectively; and the specificities were 76.56%, 67.19% and 73.44%, respectively. The areas under the curve (AUCs) were 0.793, 0.784, and 0.818, respectively. The specificity and AUC of the combination of the three methods were 98.44% and 0.918, respectively. Conclusion: Serum APN and D-D levels and the NLR in patients with diabetic foot ulcer infection are related to disease severity. The serum APN, D-D and NLR can be used as sensitive indicators for predicting poor patient prognosis.